Electron Donating 2,7-Carbazole Derivatives: Synthesis and Characterization - Zubair, Rizgar Maher (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2013)
Carbazoles (Cbz)s are well known electron-donating materials because of the conjugated π-electrons present in their structures, they are one of the most suitable candidates for construction of electronic devices. In the present work, we synthesized a 2,7-dibromo-N-dodecyl carbazole (dodecylcbz) via a two step procedure. In the first step, 2,7-dibromocarbazole (cbz) was synthesized (via another two step procedure–nitration of dibromobiphenyl and consequent cadogan ring closing steps). In the second step, the targeted dodecylcbz was synthesized via nucleophilic substitution. The synthesized compounds were characterized by mp, FTIR, UV-vis, NMR, and emission techniques. The FTIR spectra confirm the structures. The solubility is very high for both the cbz and dodecylcbz in all common organic solvents. The absorption spectra of both cbz and dodecylcbz show high energy forbidden S0→S2 transition absorptions with high intensity at around 240 nm comparing to π→π* electronic transition absorptions at around 303 nm, respectively in all of the common organic solvents studied. Most importantly, π→π* electronic transition absorptions of both carbazole and dodecylcarbazole were unchanged with respect to the polarity and type of the solvent. Whereas, S0→S2 transition absorptions have undergone solvent-dependent shifts. Both the cbz and dodecylcarbazole exhibited intense excimer emissions in all of the solvents. These interesting optical properties are very useful for present-day organic-based optoelectronic applications. Keywords: Carbazole, 2,7-Dibromocarbazole, Excimer Emission, Forbidden Transitions

ÖZ: Karbazoller yapılarında mevcut olan konjuge π-elektronları nedeniyle elektron-verici maddeler olarak bilinmektedirler. Bu yüzden, karbazoller elektronik cihazların yapımı için en uygun adaylardan biridir. Bu çalışmada, 2,7-dibromo-N-dodesil karbazol (dodesilcbz) iki basamakta sentezlenmiştir. İlk basamakta 2,7-dibromokarbazol (cbz) sentezlenmiştir (başka bir iki basamaklı prosedür ile – dibromofenil nitrasyonu ve Cadogan halka kapanma işlemi). İkinci basamakta hedeflenen dodesilkarbazol nükleofil yer değiştirme tepkimesi ile sentezlenmiştir. Sentezlenen bileşikler, erime noktası, FTIR, UV-vis, NMR ve emisyon teknikleri kullanılarak karakterize edilmiştir. FTIR spektrumları yapıları teyit etmektedir. Çözünürlük yaygın olarak kullanılan tüm organik çözücülerde cbz ve dodesilcbz için çok yüksektir. Karbazol ve dodesilkarbazolun yaygın olarak kullanılan tüm organik çözücülerdeki absorpsiyon spektrumlarında, 240 nm civarındaki S0→S2 yasaklanmış geçiş absorpsiyonu 303 nm civarındaki π→π* elektronik geçiş absorpsiyonu ile karşılaştırıldığında daha şiddetlidir. En önemlisi, karbazol ve dodesilkarbazolun π→π* elektronik geçiş absorpsiyonu çözücünün türü ve polaritesinden bağımsızken S0→S2 geçiş absorpsiyonu çözücüye bağlı olarak kaymaktadır. Karbazol ve dodesilkarbazol tüm çözücülerde yoğun ekzimer emisyonu sergilemiştir. Bu ilginç optic özellikler, günümüz organik-bazlı optoelektronik uygulamalar için çok kullanışlıdır. Anahtar Kelimeler: Karbazol, 2,7-Dibromokarbazol, Ekzimer Emisyonu, Yasaklanmış Geçişler.
Master of Science in Chemistry. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Chemistry, 2013. Supervisor: Prof. Dr. Huriye İcil
Keywords: Chemistry; Organic Chemistry; Organic electronics; Carbazole; 2,7-Dibromocarbazole; Excimer Emission; Forbidden Transitions